Wine Farms between Specialisation and Diversification - Empirical Insights from Switzerland and Romania - Stefan Mann; Petrica Stefan (German Journal of Agricultural Economics (GJAE), 2018)
While economists often emphasise the advantages of specialisation, power asymmetries between farmers and processors and risk mitigation are arguments for diversification in the primary sector. Swiss and Romanian wine farms are used to test the hypothesis that pressing grapes and processing them into wine will be financially advantageous for wine farms, while other diversification strategies are less promising. Survey results verify this hypothesis for Switzerland. For Romania, a winery on the farm and a positive attitude towards wine tourism are advantageous. Some amenities on the farm such as events or playgrounds allow higher prices to be charged, but this does not result in a better financial situation. Another success factor for both countries is the combination with arable farming. The conclusion is that targeted and well-adapted diversification strategies on wine farms can be recommended.
Keywords: 330